Analisis Manajemen Kompetisi Olimpiade Bidang Ilmu Biologi dalam Membimbing Peserta Olimpiade - Aminah Chandra Kasih; Mohamad Muspawi (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is motivated by the achievements achieved by MAN Insan Scholar Jambi students at the national student olympiad and national student competition in the field of biology. This research aims to analyze the management of biology instructors in guiding students at MAN Insan Scholar Jambi. The research was carried out for two weeks from October – November 2023. This research is included in research on events in the field or can be called field research using qualitative research. The informant for data collection was the biology olympiad teacher. The results of this research illustrate that the role of the olympiad teacher in the field of biological sciences at MAN Insan Cendikia Jambi is not just as a teacher, but also as a facilitator and learning friend for the participants. Through structured planning of coaching activities, careful participant selection strategies, and involvement in routine activities and competitions, teachers prove their commitment and involvement in developing students' potential. A holistic approach in identifying participants' skill and knowledge needs, together with tailored learning methods, indicates a serious effort in optimizing participants' abilities.